Oral Antibiotics Alone versus Oral Antibiotics Combined with Mechanical Bowel Preparation for Elective Colorectal Surgery: A Propensity Score-Matching Re-Analysis of the iCral 2 and 3 Prospective Cohorts - Marco Catarci; Stefano Guadagni; Francesco Masedu; Massimo Sartelli; Leonardo Antonio Montemurro; Gian Luca Baiocchi; Giovanni Domenico Tebala; Felice Borghi; Pierluigi Marini; Marco Scatizzi; the Italian ColoRectal Anastomotic Leakage (iCral) (MDPI AG, 2024)
The evidence regarding the role of oral antibiotics alone (oA) or combined with mechanical bowel preparation (MoABP) for elective colorectal surgery remains controversial. A prospective database of 8359 colorectal resections gathered over a 32-month period from 78 Italian surgical units (the iCral 2 and 3 studies), reporting patient-, disease-, and procedure-related variables together with 60-day adverse events, was re-analyzed to identify a subgroup of 1013 cases (12.1%) that received either oA or MoABP. This dataset was analyzed using a 1:1 propensity score-matching model including 20 covariates. Two well-balanced groups of 243 patients each were obtained: group A (oA) and group B (MoABP). The primary endpoints were anastomotic leakage (AL) and surgical site infection (SSI) rates. Group A vs. group B showed a significantly higher AL risk [14 (5.8%) vs. 6 (2.5%) events; OR: 3.77; 95%CI: 1.22-11.67; p = 0.021], while no significant difference was recorded between the two groups regarding SSIs. These results strongly support the use of MoABP for elective colorectal resections.